OPTIMIZATION OF LEAN CONSTRUCTION-BASED PROJECT PERFORMANCE ON HIGH-RISE BUILDING STRUCTURE WORK OF PRECAST AND HALF SLAB BEAM SYSTEMS USING THE RELATIVE IMPORTANCE INDEX (RII) METHOD - Moh. Sholahuddin (Jurnal Scientia, 2023)
In the construction of high rise buildings, beams and slabs are one of the main elements where both function is as a load distribution element. Using precast beams and half slabs simultaneously for high-rise buildings is a feasible innovation because it is expected that usingo precast elements together will improve project performance. However, in practice there are several obstacles in using of this method so that work pr oductivity becomes less than optimal. Using a questionnaire-based data analysis method, this study examines the application of lean construction to use these materials. The results of the study's result indicate that the application of lean construction to high-rise building structures for precast beam and half slab systems has been proven to have produced 7 variables with 35 waste factors. must be watched out and eliminated in the implementation of the work because all these factors and variables can reduce project performance so that if they can be eliminated it will increase the productivity of project performance.